Vorsprung durch Technik: multi-display learning spaces and art-historical method - Bligh, Brett; Lorenz, Katharina (2010)
The trajectory and heuristic success of Art History as a discipline has always been inseparably linked to the technical means of visualizing the material that is at its core. When in the late 19th century first analogous, then double-slide projection was introduced, associated methodological opportunities were identified and formalised through debate within the discipline. This led to a profound change in the discipline’s analytical rhetoric, installing vis-à-vis or comparative viewing as the primary mode of art-historical inquiry throughout the 20th century. In contrast, the more recent move to PowerPoint or equivalent linear digital presentation has not received the same form of attention within Art History. Whilst the impact on disciplinary rhetoric is undeniable, the affordances these technologies offer to the analytical frameworks of Art History are not well understood, nor have they been used to develop the discipline’s methodology further.